Leadership Behaviours and Academic Performance in Iraqi Public Universities: A Review - Almayali, Hakim Hsoonee (Information Management and Business Review, 2012)
In line with the â€œNational Strategy 2009-2013â€ launched by the Iraqi Ministry of Higher Education and Scientific Research (MOHESR), this study proposed to investigates the behaviour of university leaders (transformational leadership or transactional leadership behaviour) in enhancing academic performance of Iraqi public universities (including teaching, research, service, and staff satisfaction). A review of the literature suggests that there is positive relationship between leadership behaviour and academic performance in higher education; however, there is a dearth of studies investigating this relationship. The results are expected to show that leadership behaviour has positive relationship on academic performance in Iraqi HEIs. (98 words)